2017
DOI: 10.1111/resp.13065
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose prednisolone after intravenous methylprednisolone improves prognosis of acute exacerbation in idiopathic interstitial pneumonias

Abstract: We concluded that a dose of PSL ≥ 0.6 mg/kg after i.v. high-dose methylprednisolone therapy should be recommended for the treatment of AE-IIPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…1 We agree that 'it is time to debate about corticosteroids in AE of idiopathic pulmonary fibrosis (IPF) (AE-IPF)'. We believe that our results may stimulate debate regarding the treatment of AE-IPF.…”
Section: From the Authorsmentioning
confidence: 99%
“…1 We agree that 'it is time to debate about corticosteroids in AE of idiopathic pulmonary fibrosis (IPF) (AE-IPF)'. We believe that our results may stimulate debate regarding the treatment of AE-IPF.…”
Section: From the Authorsmentioning
confidence: 99%
“…Reduced forced vital capacity (FVC), non-smoker, and elevation of Krebs von den Lungen-6 (KL-6) have been reported as candidate risk factors for AE [15][16][17][18]. Recently, Arai et al [19] reported a diffuse HRCT pattern, lower serum IgG, and higher serum surfactant protein-D in AE diagnosis. Long-term oxygen therapy (LTOT) before AE and positive pressure ventilation (PPV) use for AE were significant poor prognostic factors [19].…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…Recently, Arai et al [19] reported a diffuse HRCT pattern, lower serum IgG, and higher serum surfactant protein-D in AE diagnosis. Long-term oxygen therapy (LTOT) before AE and positive pressure ventilation (PPV) use for AE were significant poor prognostic factors [19].…”
Section: Clinical Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the subgroup that received the highest doses of corticosteroids tends to show a lower survival rate after 90 days (36% vs 22%) (Supplementary Information). 1 Additionally, we do not have any data regarding the cumulative effect of the total dose of steroids received by the patient, to demonstrate that in fact it could have a greater effect on the 90-day survival rate than the initial dose, especially in relation to adverse events. In addition, it is worth noting that the high dose of corticosteroids only improves survival in the non-ventilated patients.…”
mentioning
confidence: 99%